A systematic review and synthesis of qualitative research: the influence of school context on symptoms of attention deficit hyperactivity disorder. Issue 1 (2nd January 2016) - Gwernan-Jones, Ruth; Moore, Darren A.; Cooper, Paul; Russell, Abigail Emma; Richardson, Michelle; Rogers, Morwenna; Thompson-Coon, Jo; Stein, Ken; Ford, Tamsin J.; Garside, Ruth
Abstract : This systematic review and synthesis of qualitative research explored contextual factors relevant to non-pharmacological interventions for attention deficit hyperactivity disorder (ADHD) in schools. We conducted meta-ethnography to synthesise 34 studies, using theories of stigma to further develop the synthesis. Studies suggested that the classroom context requiring pupils to sit still, be quiet and concentrate could trigger symptoms of ADHD, and that symptoms could then be exacerbated through informal/formal labelling and stigma, damaged self-perceptions and resulting poor relationships with staff and pupils. Influences of the school context on symptoms of ADHD were often invisible to teachers and pupils, with most attributions made to the individual pupil and/or the pupil's family. We theorise that this 'invisibility' is at least partly an artefact of stigma, and that the potential for stigma for ADHD to seem 'natural and right' in the context of schools needs to be taken into account when planning any intervention.